Spatio-temporal Evolution and Scenario Prediction of Carbon Storage in Typical Wetlands in Poyang Lake Region - Wei Zezhu; Dong Bin; Xu Haifeng; Xu Zhili; Lu Zhipeng; Liu Xiao (Shuitu baochi tongbao)
[Objective] The temporal and spatial characteristics of carbon storage in the Poyang Lake wetland ecosystem were analyzed in order to provide scientifically based recommendations to protect Poyang Lake wetlands in the future and to produce regional “carbon peak and carbon neutrality”. [Methods] InVEST and GeoSoS-FLUS models were combined to calculate carbon storage of typical wetlands in the Poyang Lake region from 2000 to 2020, and to predict carbon storage changes in 2030 under natural development scenarios and ecological protection scenarios. The factors driving carbon storage changes were determined by means of the geographic detector model. [Results] ① The carbon reserves of typical wetlands in the Poyang Lake region in 2000, 2010 and 2020 were 2.42×106 t 2.48×106 t and 2.46×106 t, respectively. ② The high carbon reserves were concentrated in the central and western forests, while the low carbon reserves were concentrated in the east, central, western and northern lakes. ③ Land use was the dominant factor affecting carbon storage transfer. The explanatory power of vegetative cover type with respect to carbon storage transfer followed the order of marsh grassland> marshland>forest land>cultivated land. ④ Compared with the natural development scenario, the change rate of carbon storage for the ecological protection scenario changed from -17.81% to -1.09% during the period from 2020 to 2030. [Conclusion] Reasonable ecological protection policies can effectively guarantee the carbon sequestration capacity of wetlands. Land use control practices should be strengthened and ecological protection measures should be implemented as as to guarantee improvement in regional carbon storage capacity.